The identification of adenylyl cyclase modulators as potential receptors for 6-nitrodopamine in human-induced pluripotent stem cell (hiPSC)-derived cardiomyocytes and their relevance in heart inotropism - Cipollone, Irene; Monaco, Vittoria; Britto-Júnior, José; Lima, Antonio Tiago; Antunes, Edson; Pupo, Andre Sampaio; Iacobucci, Ilaria; Cozzolino, Flora; Monti, Maria; Parisi, Silvia; Divisato, Giuseppina; Cascone, Emanuela; et al. (Frontiers in Pharmacology, 2025)
6-Nitrodopamine (6-ND) has potent positive chronotropic and inotropic effects. At a very low dose, i.e., 10 fM, it causes potentiation of the positive chronotropic effects induced by catecholamines in the rat atria, indicating a distinct mechanism of action. Cyclase-associated proteins (CAP-1 and CAP-2) are potential receptors for 6-ND in human cardiomyocytes. Since cyclic 3′,5′-cyclic adenosine monophosphate (cAMP) plays a fundamental role in the positive inotropic effects of classical catecholamines, it was further investigated whether 6-ND potentiates the positive inotropic effects induced by classical catecholamines in the rat isolated perfused heart. Human-induced pluripotent stem cell (hiPSC)-derived cardiomyocytes were harvested and lysed, and following appropriate separation procedures, membrane proteins were incubated with 6-ND-derivatized agarose, centrifuged, and the proteins retained in the agarose eluted with 6-ND (1 mM). The proteins isolated from the chemical pulldown assay were fractionated by SDS-PAGE, the bands were cut and hydrolyzed in situ with trypsin, and then separated and sequenced. A total of 817 proteins were generated, and following screening using UniProt “Retrieve/ID Mapping” function and Gene Ontology cellular component category, 124 proteins were identified as membrane proteins. These experiments identified three proteins that modulate adenylyl cyclase (AC) activity (CAP-1, CAP-2, and STIM1), which are compatible with the pharmacological findings reported for 6-ND in the rat heart. As expected, 6-ND strongly potentiates the inotropic effect induced by noradrenaline in Langendorff’s preparation. In conclusion, 6-ND-induced potentiation of catecholamine-induced chronotropic and inotropic effects is due to the modulation of adenylyl cyclase activity, probably via direct interactions with CAP-1 and CAP-2.